2015
DOI: 10.1371/journal.pone.0137336
|View full text |Cite
|
Sign up to set email alerts
|

Post-ART Symptoms Were Not the Problem: A Qualitative Study on Adherence to ART in HIV-Infected Patients in a Mozambican Rural Hospital

Abstract: ObjectiveThe objective of this qualitative study was to explore how clinical symptoms may affect adherence to antiretroviral therapy (ART) in HIV patients, and to explore factors, perceptions and attitudes related to adherence to therapy.DesignA qualitative study was carried out in the context of the prospective cohort study “Evaluation of Immune Reconstitution Following Initiation of Highly Active Antiretroviral Treatment in Manhiça, Mozambique”. In-depth Interviews were conducted twice in a sub-sample of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Participants’ narratives show that side effects are the most reported reason for non-adherence. This finding is consistent with previous studies [ 39 41 ]; however, a study shows that experiencing symptoms after starting treatment was not a barrier to adherence to ART [ 42 ]. The commonly reported side effect of ARV in this study was vomiting.…”
Section: Discussionsupporting
confidence: 93%
“…Participants’ narratives show that side effects are the most reported reason for non-adherence. This finding is consistent with previous studies [ 39 41 ]; however, a study shows that experiencing symptoms after starting treatment was not a barrier to adherence to ART [ 42 ]. The commonly reported side effect of ARV in this study was vomiting.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, one of the important patient-reported cross-cutting issues that emerged through all steps of the cascade was the relationship between the health system and the patient, which had a bivalent and cumulative effect along the continuum. On one hand, responses from PLWHIV from our study reflected a strong authoritarian and vertical relationship where the health system was in the position of power and the patient occupied the lowest level and complied with the norms and laws [46] of the hospital. Indeed, studies conducted in Uganda and Sudan shown that less half of the patients and health providers are aware of the existence of national Charter of patients’ rights, increasing client vulnerability [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Retention in care is improved by feeling better after ART initiation, confidence in the health system and support from family and providers. 27 Communication about continuing treatment despite feeling better also helps. 24 Barriers to retention include provider authoritarianism, which limits patient autonomy and engagement in their healthcare, and the adverse effects of ART.…”
Section: Challenges For Achieving 95-95-95 In Esamentioning
confidence: 99%
“… 24 Barriers to retention include provider authoritarianism, which limits patient autonomy and engagement in their healthcare, and the adverse effects of ART. 27 Men across the region are a hard-to-reach group; they test less, and more abandon ART after initiation. 22 There are additional complexities related to paediatric care, such as the health literacy of parents and their confidence in managing HIV.…”
Section: Challenges For Achieving 95-95-95 In Esamentioning
confidence: 99%